Factors influencing the supportive care needs of female patients with genital cancer in South Korea - Son, Yu-Jung; Nam, Keum-Hee; Shim, JaeLan (Medicine (Baltimore), 2023)
Genital cancers are particularly important compared to other cancers because of the psychological impact they have on the individual. This study investigated the complexity in illness and quality of life among female genital cancer patients and determined the effects of these factors on supportive care needs to provide evidential data for the development of nursing intervention strategies to reduce supportive care needs in female genital cancer patients. This cross-sectional study collected data from July 22 to August 17, 2021. The study subjects were 103 female outpatients and inpatients aged 19 years or older who were treated for cervical cancer, endometrial cancer, ovarian cancer, or other female genital cancers such as vulvar cancer and vaginal cancer in a university hospital in Korea. The data were analyzed with t-tests and Scheffé's test using SPSS 26.0. The factors affecting supportive care needs were examined using hierarchical regression. The average age of the subjects was 56.41 (±9.91) years. Cervical cancer was the most common diagnosis at 42.7%, followed by ovarian cancer at 34.0%, and endometrial cancer at 21.4%. The factors affecting supportive care needs included a middle school education or below (β = 0.21, P = .028), unemployment (β = 0.23, P = .018), complexity in illness (β = 0.32, P < .001), and quality of life (β = −0.68, P < .001). Developing a strategy for managing the complexity in illness and quality of life caused by various variables including disease stage and type of treatment is necessary to reduce the supportive care needs of female genital cancer patients. Improving their quality of life through effective communication with healthcare providers is essential.